ANALISIS MOTIVASI DALAM PENINGKATAN KINERJA KARYAWAN PADA PERUMDA BANK GRESIK - Rahmawati, Ramadiva; Cahyadi, Nur (Jurnal Bisnis dan Kewirausahaan, 2024)
One of the phenomena seen in Perumda Bank Gresik is problems regarding employee performance. Based on performance data in the form of KPI from several employees, it was identified that employees had not been able to maximize their performance in certain aspects, even though Perumda Bank Gresik was facing intense business competition. This allegedly occurs because there are employees who experience stress, excessive pressure, and other factors which are included in aspects that inhibit work motivation. This research aims to analyze the relationship between work motivation and employee performance in terms of several factors from each variable. The method used in this research is descriptive statistical research. Data collection was carried out by means of limited observation and interviews. The research was conducted at Perumda Bank Gresik during the period August – October 2023. Based on the results of the analysis, it was found that the work motivation possessed by employees was oriented towards limited needs, especially salary or income, so that employees did not prioritize work assessment, thereby impacting employee performance.